Trends of food and agricultural input prices in Eastern Africa - Wanjiku, Julliet; Njagi, Lincoln; Kirui, Desmond (International Food Policy Research Institute, 2016)
This brief analyses the trends of food and input prices in the Eastern Africa region from year to year with 2007 as the base year. The brief provides information on the price changes in food and inputs at country and regional level to facilitate effective policy related decision making.